THE FORMING OF CASTELLUM-TYPE CASTLES AND FOUR-UNIT BUILDING COMPLEXES WITH CHAPELS IN SECULAR POWER CENTRES OF COURLAND AND THE STATE OF THE TEUTONIC ORDER - Ozola, Silvija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
In the noble families houses, a sacral room or a separate volume made for relics’ storage or prayers started to call the chapel (German: Kapelle, Latin: capella). The name for this building type was borrowed from the Latin words cappa, capa. The knights for implementation of its policy on conquered lands inhabited by the Balts founded economically independent castles of stone that included chapels. According to regulations of castellum’s planning, the chapel had to be situated on the east side of the structure. In Livonia and the State of the Teutonic Order, the location of castles and cult buildings influenced layouts of town centres. Research goal: analysis the impact of cult buildings on layouts and spatial structures of castles and fortified centres to determine common and different characteristics in Livonia and the State of the Teutonic Order. Research problem: the influence of sacred buildings’ location on layouts of castles, built by the Teutonic Order. has not well researched. Research novelty: structures of the Teutonic Order’s fortresses are studied in the context of Italian architecture. Research methods: studies of urban planning cartographic materials, archive documents, projects, published literature and inspection of buildings in nature.